New genus and species of cavernicolous cockroach (Blattaria, Nocticolidae) from Vietnam - Vidlička, Ľubomír; Vršanský, Peter; Kúdelová, Tatiana; Kúdela, Matúš; Deharveng, Louis; Hain, Miroslav (Zootaxa, 2017)
The new, small cavernicolous species Helmablatta louisrothi gen. et sp. n. (Nocticolidae) from the Tan-Phu cave (Vietnam) is one of the most morphologically interesting cockroaches. The extremely modified upstanding tergal gland composite from three tergites and may serve for gripping the female head during copulation. This presumption is supported by the presence of a central big hook on tergite 8. Furthermore, both wing pairs are uncommonly adapted to help releasing sex pheromones without raising the wings. Histone 3 DNA-based maximum likelihood analyses indicate a recent origin and close phylogenetic relationship between Nocticola spp. and Helmablatta sp.—consistent with the Quaternary age of the source lava tubes.